American Prometheus : the triumph and tragedy of J. Robert Oppenheimer - Bird, Kai.; Sherwin, Martin J. (New York : A.A. Knopf, 2005)
The first full-scale biography of the "father of the atomic bomb, " the brilliant, charismatic physicist who led the effort to capture the fire of the sun for his country in time of war. After Hiroshima, he became the most famous scientist of his generation--an icon of modern man confronting the consequences of scientific progress. He created a radical proposal to place international controls over atomic materials, opposed the development of the hydrogen bomb and criticized the Air Force's plans to fight a nuclear war. In the hysteria of the early 1950s, his ideas were anathema to powerful advocates of a massive nuclear buildup, and people such as Edward Teller and FBI director J. Edgar Hoover worked behind the scenes to obtain a finding that he could not be trusted with America's nuclear secrets. This book is both biography and history, significant to our understanding of our recent past--and of our choices for the future.
I: "He received every new idea as perfectly beautiful" -- "His separate prison" -- "I am having a pretty bad time" -- "I find the work hard, thank God, & almost pleasant" -- "I am Oppenheimer" -- "Oppie" -- "The nim nim boys" -- II: "In 1936 my interests began to change" -- "[Frank] clipped it out and sent it in" -- "More and more surely" -- "I'm going to marry a friend of yours, Steve" -- "We were pulling the new deal to the left" -- "The coordinator of rapid rupture" -- "The Chevalier affair" -- III: "He'd become very patriotic" -- "Too much secrecy" -- "Oppenheimer is telling the truth ..." -- "Suicide, motive unknown" -- "Would you like to adopt her? '' -- "Bohr was God, and Oppie was his prophet" -- "The impact of the gadget on civilization" -- "Now we're all sons-of-bitches" -- IV: "Those poor little people" -- "I feel I have blood on my hands" -- "People could destroy New York" -- "Oppie had a rash and is now immune" -- "An intellectual hotel" -- "He couldn't understand why he did it" -- "I am sure that is why she threw things at him" -- "He never let on what his opinion was" -- "Dark words about Oppie" -- "Scientist X" -- "The beast in the jungle" -- V: "It looks pretty bad, doesn't it?" -- "I fear that this whole thing is a piece of idiocy" -- "A manifestation of hysteria" -- "A black mark on the Escutcheon of our country" -- "I can still feel the warm blood on my hands" -- "It was really like a never-never-land" -- "It should have been done the day after trinity" -- Epilogue: "There's only one Robert."
Includes bibliographical references (p. [685]-699) and index.
Keywords: Oppenheimer, J. Robert, -- 1904-1967.; Physicists -- United States -- Biography; Atomic bomb -- United States -- History; Science -- Political aspects -- United States -- History -- 20th century; United States -- History -- 20th century; Manhattanproject